BALANCE EXAMINATION OF THE DASAWISMA GROUP OF NGAJEG, TIRTOMARTANI, KALASAN, SLEMAN REGENCY - Utami, Jacoba Nugrahaningtyas Wahjuning (LPPM Sekolah Tinggi Ilmu Kesehatan Yogyakarta, 2023)
Background, Body balance is the ability of a person to control or maintain the position of the body so as not to fall. Balance is a very important component for a person in carrying out daily activities. An estimated 13% of adults reported that balance disorders from 65-69 years of age would increase to 46% in those aged 85 and over. Balance disorder is one of the most important reasons that are the cause of the risk of falling The purpose is to find out the description of factors that affect body balance in the community of Ngajeg Village, Tirtomartani, Kalasan District, Sleman Regency Method, Balance check is carried out on October 7, 2022. The data source is derived from the primary data. Data collection technique by accidental sampling, by measuring the length of standing on the balance board, the examination is carried out on the members of the homestead dasa who are present at the time of the examination by the participant standing with one of his legs and measured for a long time staying in the position of not falling / falling. The measuring instruments used are balance tools, stopwatches, stationery and master tables. The results of 10 participants who took the body balance examination were obtained by all (100%) participants were women. The age of 8 participants (80%) was less than 60 years, as many as 7 respondents (70%) had menoposue, while for balance disorders as many as 3 (30%) disorders in 1 foot, 5 (50%) had balance disorders on their 2 feet and 2 (20%) patients were normal. For the history of disease, both falling and pain in the limbs, 7 (70%) respondents experienced balance disorders and experienced pain or had fallen. And as many as 3 respondents (30 %) had a balance disorder and a history of DM disease Conclusion, age, menopause, history of falls and pain as well as a history of DM can affect balance disorders